The pericranial flap for inner lining of full-thickness nasal defects: a retrospective cohort study. Issue 5 (6th May 2023) - Lewis, T; Care, R; Kuta, V; Secord, S; Trites, J; Corsten, M; Rigby, M; Taylor, S M
Abstract: Background: Effective nasal reconstruction requires skin and soft tissue cover, cartilage or bone structure, and mucosal lining. Ideal lining is thin, pliable and vascularised, making reconstruction challenging. This paper presents the first case series with long-term outcomes of pericranial flaps used as inner lining for nasal reconstruction. Methods: Patients undergoing paramedial forehead flaps from 2007 to 2019 were identified using second-stage nasal reconstruction billing codes. Patients with pericranial flaps for lining, for whom there were data on resulting outcomes and complications, were identified. Results: Sixty-six patients underwent second-stage nasal reconstruction. Eighteen patients had paramedian forehead and pericranial flaps for inner lining reconstruction. The flap lining had no immediate post-operative complications. Three patients suffered partial to major reconstructive failure post radiotherapy. Other complications included nasal stenosis and orocutaneous fistula. Conclusion: Combined with paramedian forehead flaps, the pericranial flap is reliable as inner lining for nasal reconstruction. It is easily accessible and useful in resections with limited mucosal options.